PENERAPAN PENDEKATAN KONTEKSTUAL BERBANTUAN LEMBAR KERJA SISWA (LKS) TERHADAP PENINGKATAN HASIL BELAJAR SISWA DI SMA NEGERI 6 PADANGSIDIMPUAN - Tuah, Sahlan; Harahap, Andes Fuady Dharma; Ariaji, Rizky (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The problem in this study is that the learning process in the classroom is still carried out conventionally, where learning is still dominated by teachers. So far, students learn science only based on the material in the textbook and are very far from the real life of students The purpose of this study is to determine the improvement of student biology learning outcomes through the application of a contextual approach to Cell Reproduction material in class XII of SMA Negeri 6 Padangsidimpuan for the 2021-2022 academic year. This type of research is Classroom Action Research. Where the subject of the study was class XII students of SMA Negeri 6 Padangsidimpuan consisting of 29 students. While data collection techniques and tools are tests and observations. Based on the results of the biology learning outcomes test of cycle I students of 68.9% and cycle II of 82.7%. And the results of an increase in student activity levels in cycle I by 61.7% and in cycle II by 76.3% then an increase in teacher activity in managing learning cycle I by 73.6% and cycle II by 80%.